Fabrication of a Fe2O3 Nanoparticles Implantation‐modified Electrode and its Applications in Electrochemical Sensing. Issue 5 (8th December 2015) - Yuan, Mengwei; Li, Jingzhe; Yu, Yanan; Fu, Yingyi; Fong, Anna; Hu, Jingbo
Abstract: A novel Fe2 O3 modified indium tin oxide electrode (Fe2 O3 /ITO) was fabricated by iron ion‐implantation method first, and then annealed at 300 °C. Fe2 O3 /ITO reveals good catalytic performance toward hydrogen peroxide (H2 O2 ) in phosphate buffer solution due to the Fe(II)/Fe(III) redox couple. Amperometric response shows a linear dependency on the H2 O2 concentration ranging up to 360 μM with a detection limit of 0.3 μM. Moreover, electrocatalytic activity based on rarely reported higher oxidation states of iron (tentatively assigned to Fe(IV)) was shown to allow the reliable detection of glucose and cysteine. The results show promising application potential of the proposed electrode. Abstract :